PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VB SDN 032 KUALU - Tri Kurnia; Lazim N Lazim N; Guslinda Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research was the low student learning outcomes IPS, from 28 students in the class only 12 students on the KKM. KKM to social learning is 70. Based on the problem, the research have done to repair learning process with cooperative script model. The research is classroom action research (PTK). The result show that in cycle I at the first meeting percentage of teacher activity is 58,33% and at the second meeting the percentage to increase become 75,00%. In cycle II at the first meeting percentage of teacher activity is 83,33 % and at the second meeting the percentage to increase become 91,67%. The students activity are increase too. In cycle I at the first meeting percentage of students activity is 54,17% and at the second meeting the percentage to increase become 66,67%. In cycle II at the first meeting percentage of students activity is 79,17 % and at the second meeting the percentage to increase become 87,50%. The average result of social learning before research is 62,96 and at the cycle I become 68,57 with percentage is 8,91%. In cycle II, the result social learning become 78,93 with percentage is 25,36%. Based on the result research, it can be concluded that the implementation of cooperative script model can increase the result of social learning at class VB Elementary School 032 Kualu.Key Words: Coorperative Script, Student Achivement the Result of IPS Studies